Indeno[1, 2‐b]carbazole as Methoxy‐Free Donor Group: Constructing Efficient and Stable Hole‐Transporting Materials for Perovskite Solar Cells. Issue 44 (16th September 2019) - Wang, Jialin; Zhang, Heng; Wu, Bingxue; Wang, Zhihui; Sun, Zhe; Xue, Song; Wu, Yongzhen; Hagfeldt, Anders; Liang, Mao
Abstract: With perovskite‐based solar cells (PSCs) now reaching efficiencies of greater than 20 %, the stability of PSC devices has become a critical challenge for commercialization. However, most efficient hole‐transporting materials (HTMs) thus far still rely on the state‐of‐the‐art methoxy triphenylamine (MOTPA) donor unit in which methoxy groups usually reduce the device stability. Herein, a carbazole‐fluorene hybrid has been employed as a methoxy‐free donor to construct organic HTMs. The indeno[1, 2‐b]carbazole group not only inherits the characteristics of carbazole and fluorene, but also exhibits additional advantages arising from the bulky planar structure. Consequently, M129, endowed with indeno[1, 2‐b]carbazole simultaneously exhibits a promising efficiency of over 20 % and superior long‐term stability. The hybrid strategy toward the methoxy‐free donor opens a new avenue for developing efficient and stable HTMs. Abstract : Balancing act : The indeno[1, 2‐b]carbazole donor not only combines the characteristics of carbazole and fluorene, but also exhibits excellent thermal stability and high hole mobility as a result of the bulky planar structure. Hole‐transporting materials based on this methoxy‐free donor demonstrate a high efficiency and stability simultaneously, providing a promising strategy for developing efficient and stable perovskite‐based solar cells.